Sub-millimeter detection of a Galactic center cool star IRS 7 by ALMA. (9th March 2020) - Tsuboi, Masato; Kitamura, Yoshimi; Tsutsumi, Takahiro; Miyawaki, Ryosuke; Miyoshi, Makoto; Miyazaki, Atsushi
Abstract: IRS 7 is an M red supergiant star which is located at ${5{^{′ ′}_{.}}5}$ north of Sagittarius A$^*$ . We detected firstly the continuum emission at $340\:$ GHz of IRS 7 using the Atacama Large Millimeter/submillimeter Array (ALMA). The total flux density of IRS 7 is $S_{\, ν} =448± 45\, μ$ Jy. The flux density indicates that IRS 7 has a photosphere radius of $R=1170± 60\, R_{\odot }$, which is roughly consistent with the previous Very Large Telescope Interferometer measurement. We also detected a shell-like feature with a northern extension in the H30α recombination line using ALMA. The electron temperature and electron density of the shell-like structure are estimated to be $\bar{T}^* _e=4650± 500\:$ K and $\bar{n}_e=(6.1± 0.6)× 10^4\:$ cm$^{-3}$, respectively. The mass loss rate is estimated to be $\dot{m}\, \, \sim 1× 10^{-4}\, M_{\odot }\:$ yr$^{-1}$, which is consistent with a typical mass loss rate of a pulsating red supergiant star with $M = 20$ –$25\, M_{\odot }$ . The kinematics of the ionized gas would support the hypothesis that the shell-like structure made by the mass loss of IRS 7 is supersonically traveling in the ambient matter towards the south. The brightened southern half of the structure and the northern extension would be a bow shock and a cometary-like tail structure, respectively.